MOTIVATION IN THE FORMING OF JUNIOR PUPILS' INTEREST TO FOREIGN LANGUAGE COMMUNICATIVE ACTIVITY - Tamara Marchii-Dmytrash (Vasyl Stefanyk Precarpathian National University, 2018)
The place of motivation in the forming of junior pupils' interest to foreign language communicative activity is substantiated in the article. It is determined that one of the effective means of forming the motivation and organizing foreign language activity in primary school is the didactic game. The content of the concept "foreign language communicative activity" is concretized. The examples of psycho-corrective and communicative-game exercises, which would promote the forming of interest to communicative foreign-language activity are presented. Key words: interest, motive, motivation, foreign language, primary school, foreign language communicative activity, foreign language teacher, junior schoolchildren.